Adoption of NPD process improvement concepts in industry: Status review of automotive suppliers in Turkey - 2008 - (:unkn) unknown (My University, 2009)
In this paper, we present our findings of a survey exploring the adoption of the new product development process improvement concepts in the automotive suppliers sector in Turkey. With this investigation, we aim to uncover differences in the way suppliers are adopting new product development (NPD) process improvement concepts. Our results indicate that indeed the adoption of the concepts varies across suppliers, and two important factors explaining, in part, this result are: (1) supplier involvement in design, and (2) the potential branding impact of the part/modules supplied. Copyright © 2009 by ASME.